(untitled) - Huang, Yang H. (New Jersey, 2004)
This up-to-date book covers both theoretical and practical aspects of pavement analysis and design. It includes some of the latest developments in the field, and some very useful computer software—developed by the author—with detailed instructions. Specific chapter topics include stresses and strains in flexible pavements, stresses and deflections in rigid pavements, traffic loading and volume, material characterization, drainage design, pavement performance, reliability, flexible pavement design, rigid pavement design, design of overlays, theory of viscoelasticity, theory of elastic layer systems, Superpave, pavement management systems, and an introduction to the 2002 Pavement Design Guide. For practicing engineers in the design of pavements and raft foundations.
Keywords: Pavements,Structural analysis (engineering); Design and construction